Toll-like receptor (TLRs) agonists and antagonists for COVID-19 treatments - Liu, Zhi-Mei; Yang, Ming-Hui; Yu, Kun; Lian, Zheng-Xing; Deng, Shou-Long (Frontiers in Pharmacology, 2022)
Severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) rapidly infects humans and animals which make coronavirus disease 2019 (COVID-19) a grievous epidemic worldwide which broke out in 2020. According to data analysis of the other coronavirus family, for instance severe acute respiratory syndrome SARS coronavirus (SARS-CoV), can provide experience for the mutation of SARS-CoV-2 and the prevention and treatment of COVID-19. Toll-like receptors (TLRs) as a pattern recognition receptor (PRRs), have an indispensable function in identifying the invader even activate the innate immune system. It is possible for organism to activate different TLR pathways which leads to secretion of proinflammatory cytokines such as Interleukin 1 (IL-1), Interleukin 6 (IL-6), Tumor necrosis factor α (TNFα) and type Ⅰ interferon. As a component of non-specific immunity, TLRs pathway may participate in the SARS-CoV-2 pathogenic processes, due to previous works have proved that TLRs are involved in the invasion and infection of SARS-CoV and MERS to varying degrees. Different TLR, such as TLR2, TLR4, TLR7, TLR8 and TLR9 probably have a double-sided in COVID-19 infection. Therefore, it is of great significance for a correctly acknowledging how TLR take part in the SARS-CoV-2 pathogenic processes, which will be the development of treatment and prevention strategies.